The Role of Digital Knowledge Sharing and Tourist Destination Image in Enhancing Tourist Visits to North Sulawesi - Ivonne Angelic Umboh; Josep Palulungan (Jurnal Penelitian Ekonomi dan Bisnis, 2026)
International tourist arrivals in North Sulawesi remain significantly lower than in established destinations like Bali, highlighting the need for targeted strategies to leverage the province's rich natural and cultural assets, such as Bunaken National Park and Tarsius sanctuaries. This study examines the mediating role of Digital Knowledge Sharing (DKS) the exchange of tourism information via social media, blogs, and review platforms like TripAdvisor—in the relationship between Tourist Destination Image (TDI) and Tourist Visits (TV). Drawing on image formation theory, the research addresses a gap in mediation analyses for emerging destinations. Employing a quantitative survey design with purposive sampling of 250 tourists (visitors and potential visitors), data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0. Constructs included TDI (cognitive, affective, and conative dimensions), DKS (sharing intensity), and TV (visit intention and actualization). Results confirm significant direct effects of TDI on both DKS (β = 0.479, p < 0.001) and TV (β = 0.687, p < 0.001), but reject DKS as a mediator (indirect effect β = 0.055, p = 0.171) and its direct effect on TV (β = 0.115, p = 0.140). This study advances theory by testing a DKS mediation model in an emerging context, integrating User-Generated Content (UGC) perspectives. Practically, it recommends image-focused digital campaigns for North Sulawesi policymakers to boost visits, while addressing digital infrastructure barriers to enhance DKS efficacy.